Anisotropic and Shape-Selective Nanomaterials : Structure-Property Relationships - Hunyadi Murph, Simona E.; Larsen, George K.; Coopersmith, Kaitlin J. (Springer International Publishing : Imprint: Springer, 2017)
This book reviews recent advances in the synthesis, characterization, and physico-chemical properties of anisotropic nanomaterials. It highlights various emerging applications of nanomaterials, including sensing and imaging, (bio)medical applications, environmental protection, plasmonics, catalysis, and energy. It provides an excellent and comprehensive overview of the effect that morphology and nanometric dimension has on the physico-chemical properties of various materials and how this leads to novel applications.
Keywords: Chemistry.; Inorganic chemistry.; Nanochemistry.; Nanotechnology.; elektronické knihy; electronic books